Analisa Time Study SAW Assy Produksi Bucket PT. XYZ - Andriani, Andriani; Setyono, Fajar; Qolik, Muhammad Abdul; Suwarno, Agus (JURNAL TEKNIK INDUSTRI, 2021)
PT. XYZ is a manufacturing company that manufactures heavy equipment components made of steel plates. The level of competition in the heavy equipment components industry is getting tighter and customer demands are getting more detailed on the quality of spare parts, thus companies are required to be able to meet customer needs without neglecting the quality and quantity of production target. One of the factors to increase the efficiency of a company globally is to increase productivity, so that customer trust increases and employee welfare improves. Various methods to increase productivity, one of them by using the time study method in the SAW of Assy Bucket section to determine the standard production time, so that the best alternative working methods and optimal results can be selected. As well as policies related to bucket production so that production achievement targets can be taken easily. In addition to improving the working method, it is hoped to improve the skills of the operator so that the quality of the bucket hardening results is above average and minimize the occurrence of reject products. Operating times and waiting cranes that cause delays can be significantly reduced. From the analysis of the time study method, the average normal time is 476.7 minutes. And the standard time reduction is 954.2 minutes.